2008
DOI: 10.1038/leu.2008.189
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia suppressor function of Egr-1 is dependent on transforming oncogene

Abstract: We have shown that deregulated expression of either c-Myb or E2F-1 blocks terminal differentiation of M1 myeloid leukemia cells at the blast stage, whereas deregulated c-Myc blocks differentiation at the intermediate stage. Each of these oncogenes potentiates M1 leukemia in vivo. The zinc-finger transcription factor Egr-1 abrogates the block in M1 terminal differentiation imparted by oncogenic c-Myc or E2F-1, suppressing their leukemia-promoting function in nude mice. In this study, we asked whether Egr-1 also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…However, although several studies have shown EGR-1 promotes cancer progression, there is increasing evidence that EGR-1 may also exerts tumor suppression [42, 43]. In leukemia, EGR-1 has been implicated in the apoptosis of myeloma cells via interaction with c-JUN while it behaves as a tumor suppressor against the oncogenes E2F-1 and c-MYC [44]. EGR-1 activation by EGF inhibited MMP9 expression and lymphoma growth [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, although several studies have shown EGR-1 promotes cancer progression, there is increasing evidence that EGR-1 may also exerts tumor suppression [42, 43]. In leukemia, EGR-1 has been implicated in the apoptosis of myeloma cells via interaction with c-JUN while it behaves as a tumor suppressor against the oncogenes E2F-1 and c-MYC [44]. EGR-1 activation by EGF inhibited MMP9 expression and lymphoma growth [45].…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 is also important for development of the macrophage lineage (96). It is interesting to note that EGR-1 abrogates the block in M1 terminal differentiation imparted by oncogenic c-Myc or E2F-1, suppressing their leukemia promoting function in nude mice (97). A novel mechanism of thalidomide in the treatment of leukemia is that thalidomide could suppress leukemia cell invasion and migration by upregulation of EGR-1 (98).…”
Section: Pathogenesis Mechanism Of Aml By Egr1mentioning
confidence: 99%
“…2, Table III and Table SI), tumor suppressor genes or TFs regulating tumor suppressors were identified for all of the entities including expression of FOXO1 [22] in FL cells, PA2G4 [23] in DLBCL cells, SOX11 [24] in MCL cells, and PRDM2 [25] in CLL. Furthermore, SOX4 and EGR1, known depending on tumor type, to act both as tumor suppressors [26][27][28][29] and oncogenes [30,31] showed lower expression in CLL cells. Finally, HCL cells had a high expression of SOX4, and also a low expression of FOXP1 [32].…”
Section: B-cell Lymphoma Entities Express Unique Sets Of Transcriptiomentioning
confidence: 99%